(untitled) - Allaby, Michael (Oxford, 1992)
The book offers many entries including biochemistry, plant physiology, cytology, ecology, genetics, evolution, biogeography, Earth history, and Earth sciences; world-wide coverage of taxonomic groups - one-third of the entries are devoted to taxa, from bacteria and fungi to the main groups of flowering and non-flowering plants.
Keywords: Botany